Репродуктивний потенціал деяких представників роду Rhododendron L. - Tymchyshyn, H.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Results of study of flowering features of 16 Rhododendron L. taxa and seed productivity of 8 species introduced to Botanical Garden of Ivan Franko L’viv National University are given. The results indicate on successful adaptation of the plants to new growing conditions.